COMMUNITY MODEL IN COASTAL AREAS TO ERADICATE POVERTY IN SOUTH BOLAANG MONGONDOW AND EAST BOLAANG MONGONDOW, NORTH SULAWESI - Paruntu, Carolus P.; Tumiwa, Johan (Journal of Asean Studies on Maritime Issues, 2016)
Poverty is a social reality characterized by underdevelopment of many things associated by social, economic, cultural, political, educational and natural factors that directly influence the inability of society, thus becoming poor. Poverty reduction efforts carried out by the community empowerment approach through areas system agrotechno based without the waste products of fish, beef, biogas, crops, fish feed, organic fertilizer and marine protected areas (MPAs) in the coastal areas of the District Boltim and Bosel, North Sulawesi . The data used are primary data obtained from field survey with the help of a list of questions. The samples were 30 respondents. The analytical method used is quantitative descriptive method by using two-sample t test value pairs (paired sample t-test). The results showed that the empowerment of communities through the application area system agrotechno based without the waste products of fish, beef, biogas, crops, fish feed, organic fertilizer and marine protected areas (MPAs) in the coastal areas, there is a significant difference increase between family‟s income before and after implementation of the system agrotechno region.